Corporate social responsibility, customer orientation, and the job performance of frontline employees - Daniel Korschun; C. B. Bhattacharya; Scott D. Swain (European School of Management and Technology (ESMT), 2013)
A study involving a Global 500 company finds that frontline employees' perceptions of corporate social responsibility (CSR) can contribute to their customer orientation (self-rated) and objective job performance (supervisor-rated) by activating social identification processes. Employees identify with the organization based in part on the extent to which CSR is supported by salient and job-relevant others both internal and external to the organization. Looking internally, employees identify with the organization to the extent that they perceive management to support CSR. Looking externally, employees can identify with customers (called employee-customer identification) to the extent they perceive customers to support the company's CSR. Both effects are enhanced when employees feel CSR is an important (versus non-important) part of their self-concept. Organizational identification directly drives job performance while employee-customer identification contributes to job performance through its effects on organizational identification and customer orientation.
urn:nbn:de:101:1-201307295146
Keywords: 650; Corporate social responsibility; organizational identification; customer orientation; job performance; Corporate Social Responsibility; Beziehungsmarketing; Kundenservice; Arbeitsverhalten; Arbeitspsychologie; Mitarbeiterbindung; Gastgewerbe; Einzelhandel; USA